2015
DOI: 10.2337/dc15-0303
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Intensive Versus Conservative Glucose Control in Patients Undergoing Coronary Artery Bypass Graft Surgery: GLUCO-CABG Trial

Abstract: OBJECTIVEThe optimal level of glycemic control needed to improve outcomes in cardiac surgery patients remains controversial.RESEARCH DESIGN AND METHODSWe randomized patients with diabetes (n = 152) and without diabetes (n = 150) with hyperglycemia to an intensive glucose target of 100–140 mg/dL (n = 151) or to a conservative target of 141–180 mg/dL (n = 151) after coronary artery bypass surgery (CABG) surgery. After the intensive care unit (ICU), patients received a single treatment regimen in the hospital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
2
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(195 citation statements)
references
References 36 publications
2
159
2
32
Order By: Relevance
“…[2,4] Data from trials, [5,6] using intensive glycemic control in patients in intensive care unit (ICU) failed to show a significant improvement in mortality and in some cases, showed an augmented mortality risk. The GLUCO-CABG trial, [7] in patients after cardiac surgery also demonstrated no differences in rates of complications and death between an intensive glucose management of 100-140 mg/dL and a traditional target of 140-180 mg/dL. However, more stringent objectives as 110-140 mg/dL may be appropriate for select patients if they are achievable without meaningful risk of hypoglycemia, for example, patients with acute myocardial infarction [8] or neurological events.…”
Section: Glycemic Targets In Hospitalized Patientsmentioning
confidence: 99%
“…[2,4] Data from trials, [5,6] using intensive glycemic control in patients in intensive care unit (ICU) failed to show a significant improvement in mortality and in some cases, showed an augmented mortality risk. The GLUCO-CABG trial, [7] in patients after cardiac surgery also demonstrated no differences in rates of complications and death between an intensive glucose management of 100-140 mg/dL and a traditional target of 140-180 mg/dL. However, more stringent objectives as 110-140 mg/dL may be appropriate for select patients if they are achievable without meaningful risk of hypoglycemia, for example, patients with acute myocardial infarction [8] or neurological events.…”
Section: Glycemic Targets In Hospitalized Patientsmentioning
confidence: 99%
“…82 Using continuous insulin infusion, a significant lower rate of complications was observed in non-diabetic patients treated with intensive (target glucose level, 100-140 mg/dL) versus conservative treatment regimen (141-180 mg/dL). 83 Therefore, based on the clinical scenario, continuous insulin infusion for basal insulin coverage or BBI may be used to achieve glucose control.…”
Section: Treatment/management Of Ptdmmentioning
confidence: 99%
“…Using Glucommander it was recently shown that for patients without diabetes, complications during coronary artery grafting were less, maintaining glucose level between 100 and 140 mg/dL versus level of 141-180 mg/dL. 12 As the first step to prospectively evaluate the effect of this desired degree of glucose control in the HCT setting, we evaluated the feasibility of obtaining near normoglycemia in HCT patients using a CGGM. Despite the small number of patients enrolled on the study, we demonstrated that a narrow range of glucose levels between 100 and 140 mg/dL was attained 61% of the time while on CGGM, with only 10 episodes (0.9% of BG measurements and 0.2% of total time on study) of BG lower than 70 mg/dL and with no episodes of BG lower than 40 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recently, efforts have been made to control hyperglycemia during hospitalization, but results from clinical trials and retrospective analyses have demonstrated inconsistent outcomes associated with intensive insulin therapy. [4][5][6][7][8][9][10][11][12] There is also evidence that severe hypoglycemia (glucose o40 mg/dL) in hospitalized patients may have a detrimental effect on outcomes, including cardiac arrest, seizures, hypoglycemia-induced coma and mortality, 5,[13][14][15][16][17] thus limiting the efforts for meticulous glucose control in the hospital. In addition, recent evidence also suggests that glucose variability can be detrimental and increase mortality risk in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%